A Note on Normal Families of Meromorphic Functions Concerning Shared Values - Yuan Wenjun; Wei Jinjin; Lin Jianming (Discrete Dynamics in Nature and Society)
We study the normality of families of meromorphic functions related to a Hayman conjecture. We consider whether a family of meromorphic functions ℱ is normal in D if, for every pair of functions f and g in ℱ, f′−afn and g′−agn share the value b for n=1,2, and 3, where a and b≠0 are two finite complex numbers. Some examples show that the conditions in our results are the best possible.